Vengeance - St. James, Ian (London Fontana, 1992)
When Tom Lambert receives a summons to the Greek island paradise of a mysterious billionaire, Maurice Stanton, he is persuaded to take the reins of Stanton's entire global enterprise, which takes him on nine-year struggle for power and makes him into a man obsessed.
Keywords: Revenge -- Business People